2022
DOI: 10.3390/brainsci12101377
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset Neuronal Intranuclear Inclusion Disease with Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-Like (MELAS-like) Episode: A Case Report and Review of Literature

Abstract: Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease with highly heterogeneous manifestations. Curvilinear hyperintensity along the corticomedullary junction on diffusion-weighted images (DWI) is a vital clue for diagnosing NIID. DWI hyperintensity tends to show an anterior-to-posterior propagation pattern as the disease progresses. The rare cases of its disappearance may lead to misdiagnosis. Here, we reported a NIID patient with mitochondrial encephalomyopathy, lactic acidosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 12 We observed that encephalitis-like episodes were frequently accompanied by headache, fever, and visual disturbances, which have also been observed in previous studies. 30 , 35 - 37 Noticeably, we observed that patients with NIID experiencing encephalitis-like episodes tended to have significantly shorter repeat counts in the expanded alleles than the others ( p = 0.016, Figure 2A ). Despite the marginal p value ( p = 0.06), this negative association between the number of GGC repeats and encephalitis-like episodes was also observed in a Chinese cohort ( n = 247).…”
Section: Discussionmentioning
confidence: 79%
“… 12 We observed that encephalitis-like episodes were frequently accompanied by headache, fever, and visual disturbances, which have also been observed in previous studies. 30 , 35 - 37 Noticeably, we observed that patients with NIID experiencing encephalitis-like episodes tended to have significantly shorter repeat counts in the expanded alleles than the others ( p = 0.016, Figure 2A ). Despite the marginal p value ( p = 0.06), this negative association between the number of GGC repeats and encephalitis-like episodes was also observed in a Chinese cohort ( n = 247).…”
Section: Discussionmentioning
confidence: 79%
“…A TIA usually goes along without DWI lesions. Only a single NIID patient with a SLL has been previously reported [5] .…”
Section: Letter To the Editormentioning
confidence: 99%
“…Researchers have proposed several hypotheses regarding the pathogenesis of NIID, including the toxicity of polyamino acid proteins (17)(18)(19), toxic RNA gain-offunction (19,20), and aberrant methylation of GGC repeat sequences (21). Recently, some studies have suggested that dysfunction of ribosome biogenesis and translation and mitochondrial dysfunction might be related to the pathogenesis of NIID (22,23). However, the speci c mechanisms driving the pathogenesis of NIID remain unclear, and extensive experiments in cellular and animal models are required for further studies.…”
Section: Pathogenesis Of Niidmentioning
confidence: 99%
“…Advances in the study of disease mechanisms form the basis for the development of preventive and therapeutic interventions. It has been suggested that NIID may be associated with mitochondrial dysfunction; therefore, therapeutic measures for mitochondrial disease may be effective for patients with NIID(23). Yan et al suggested that in ammation might also play an important role in the pathogenesis of NIID(29).…”
mentioning
confidence: 99%